Breast Cancer Evolving Challenges and Next Frontiers - Valarmathi, Mani T. (IntechOpen, 2021)
In recent years, there has been substantial development in breast cancer research and its clinical applications, for example, breast cancer biology and genomics, epidemiology and prevention, early detection and screening, and diagnosis and treatment. As such, this book consolidates recent advances in breast cancer biology and therapeutics, covering a broad spectrum of interrelated subjects. Chapters cover topics such as pathobiology of breast cancer, biomarkers, in vitro models of breast cancer, pharmacotherapy, screening and management, diagnostic imaging, and more. This book is a valuable resource for medical and allied health students as well as researchers and clinicians.